Sosialisasi Pemasangan CCTV Tambahan pada Ruang Pembinaan Kemandirian Guna Meningkatkan Efektivitas Pembinaan Kemandirian di Lembaga Pemasyarakatan Kelas IIA Banyuwangi - Monica Astia Theresia Panjaitan; Kharisma Huril’in Firdaus; Prasetya Adhi Nugraha; Vivi Sylviani Biafri; Ali Muhammad; Imaduddin Hamzah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
The development of self-reliance among correctional inmates faces challenges in terms of surveillance effectiveness and order within correctional institutions. One of the main issues encountered is the lack of an optimal surveillance system, which can hinder the rehabilitation process and increase the risk of rule violations. To address this issue, a socialization program for the installation of additional CCTV cameras in the Self-Reliance Development Room at Banyuwangi Class IIA Correctional Facility was conducted. The program aimed to enhance surveillance effectiveness, create a safer rehabilitation environment, and encourage behavioral changes among inmates. The methods used in this community service project included needs analysis, coordination with correctional authorities, conducting socialization sessions for officers and inmates, and evaluating the impact of CCTV installation. The results indicate that the installation of CCTV contributes to improving inmate discipline, reducing rule violations, and strengthening transparency and accountability in the rehabilitation process. Additionally, this program fosters the emergence of local leaders among inmates who play a role in maintaining order. These findings align with social control and social learning theories, which emphasize that effective surveillance can shape individual behavior and promote compliance with established norms. In conclusion, the implementation of surveillance technology in the correctional system can serve as a strategic step in supporting inmate rehabilitation and social reintegration.